Prognostic factors for Taiwanese patients with cutaneous melanoma undergoing sentinel lymph node biopsy - Chiao-En Wu (Journal of the Formosan Medical Association, 2015)
Sentinel lymph node biopsy (SLNB) is a standard procedure in the management of clinically node-negative melanoma. However, few studies have been performed on SLNB in Asia, which is an acral melanoma-prevalent area. This study evaluated the clinicopathologic prognostic factors of disease-free survival (DFS) and overall survival (OS) in Taiwanese patients with cutaneous melanoma who received wide excision and SLNB. The prognosis of patients with false-negative (FN) SLNB was also evaluated. Methods: Malignant melanoma cases were reviewed for 518 patients who were treated between January 2000 and December 2011. Of these patients, 127 patients with node-negative cutaneous melanoma who received successful SLNB were eligible for inclusion in the study. Results: The SLNB-positive rate was 34.6%. The median DFS was 51.5 months, and the median OS was 90.9 months at the median follow-up of 36.6 months. Multivariate analysis revealed that patients whose melanoma had a Breslow thickness greater than 2 mm had a significantly shorter DFS than patients whose melanoma had a Breslow thickness of 2 mm or less [hazard ratio (HR), 3.421; p = 0.005]. Independent prognostic factors of OS were a Breslow thickness greater than 2 mm (HR, 4.435; p = 0.002); nonacral melanoma (HR, 3.048; p = 0.001); and an age older than 65 years (HR, 2.819; p = 0.036). During the follow-up period, 13 of 83 SLN-negative patients developed a regional nodal recurrence. The SLNB failure rate was 15.7% and the FN rate was 22.8%. Compared to patients with a true-positive SLNB, patients with FN SLNB had a significantly shorter DFS (p = 0.001) but no significant difference in OS (p = 0.262). Conclusion: Except for the pathologic subtypes, prognostic factors in Taiwan are similar to those used in other melanoma-prevalent countries. Identifying and closely monitoring patients at risk of nodal recurrence after a negative SLNB is important.